Effect of Chemical Reaction on Mass Transfer Embedded in a Porous Medium over an Exponentially Porous Stretching Surface - Amoo, S.A. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
The effect of chemical reaction on mass transfer embedded in porous medium is implemented over an exponentially porousstretching surface. The emerging governing equations were simplified using similarity variable function and some relevantdimensionless parameters. The modelled equations were solved using Runge-Kutta method with shooting techniques. Thiswas done by converting the modelled equations to an initial value problem and solved using Maple 18. The numericalcomputations were presented in tabular and graphical forms for variable fluid parameters controlling the flow, chemicalreaction and mass transfer. The results in form of velocity and concentration profiles, Skin friction and Sherwood numberincreased with varied parameters were discussed. The findings were compared with existing solutions and found to haveminimal errors.